NUMERICAL AND EXPERIMENTAL ANALYSIS OF UNSTEADY WORK OF U-SHAPE BOREHOLE HEAT EXCHANGER - S. A. Filatau (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Unsteady numerical model of borehole heat exchanger heat regime was developed. General numerical modeling results are borehole heat flux, heat carrier inlet temperature and average soil temperature distribution. Proposed model is based on solution of heat conduction equation in transient plane axially symmetric formulation with boundary conditions for borehole heat exchanger and undisturbed soil domain. Solution method is finite difference method. Numerical model is verified with comparisons numerical results and experimental data from developed laboratory installation for simulation unsteady heat regime of horizontal positioned U-shape ground heat exchanger in sand medium.Cooling of water is organized in ground exchanger in experiment. Experiment includes two steps. Thermal properties of sand is determined at the first stage. Thermal conductivity of sand is determined by stationary plate method, thermal diffusivity is determined by regular regime method using cylindrical calorimeter. Determined properties are used further in processing of experimental results at second step for analysis of transient work of ground heat exchanger. Results of four experiments are analyzed with different duration and time behavior of mass flow and heat carrier temperature. Divergences of experimental and simulated results for temperature of heat carrier changes in the range 0,5–1,8 %, for sand temperature in the range 1,0–2,3 %, for heat flux in the range 3,6–5,4 %. Experimental results can be used for validation of other simulation methods of ground heat exchangers. Presented numerical model can be used for analyzing of heat supply systems with heat pumps.